DIGITAL DIMENSIONS OF ECO-FRIENDLY FASHION AND INNOVATION AS DESIGN CONCEPTS OF GLOBAL BRANDS - Remenieva, Tetiana; Kolosnichenko, Olena; Skliarenko, Nataliia (Theory and practice of design, 2024)
The article examines modern fashion in the context of conscious consumption, with a view to fostering a caring attitude towards the environment, as well as analyzing the use of scientific breakthroughs and their implementation in various technologies of modern manufacturing and training. The role of branding and design elements in the innovative communication of technology and fashion is investigated. The evolution of digital fashion and the methodological concept of the new fashion direction are analyzed. An overview of the employment of modern advanced technologies in the work of creative designers of the new generation is presented. The major tendencies and prospects for development are outlined with an emphasis on the challenges of today. The research has identified and recognized the potential of Ukrainian creators and manufacturers of the fashion industry as undiscovered, therefore, young designers should join forces and set up collaborations for the sustainable development of the domestic fashion segment and focus on building the idea of community to form competitive prices and promote new brands. Purpose. The aim of the article lies in analyzing modern trends to determine the key areas in the development of the fashion as well of unique innovative projects that blend the art of fashion and technological advancements in design workflows. Methodology. The methodological basis of the study is a systematic approach, analysis of scientific, technical and regulatory information, methods of literary and analytical, systemic and structural, comparative analysis, as well as the historical method. Approach involved methods as formal, stylistic, compositional and coloristic analysis; methods of systematization of visual sources. The scientific novelty consists in performing a systematic analysis of the results of the work of leading global brands in the practical implementation of new design trends in the form of: a blend of biotechnologies and avant-garde design to be used in potential end-uses, including smart tissues, devices, biosensors; use of advanced IT technologies through digital materials, 3D prints and 3D animation software, along with animatronic robotic systems. The above is gaining massive popularity in design practice when creating luxury fashion items. The practical relevance consists in bridging the contradictions in the development of the fashion between theoretical messages and practical application, as well in revealing the scope for designing harmonious relationships in a modern environmentally oriented design concept. Analytical studies breakthroughs allow us to develop new trends in eco-concepts in the collaboration of scientists and the work of modern designers, which will contribute to the sustainable development of societal cultural messages, as well as the possibilities of creating trending patterns and designer fabrics in the laboratories of designers and scientists as the the dynamics of new trends.